2020
DOI: 10.1111/aas.13665
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ethical aspects of palliative sedation with propofol—A retrospective quantitative and qualitative study

Abstract: Background The anesthetic propofol is often mentioned as a drug that can be used in palliative sedation. The existing literature of how to use propofol in palliative sedation is scarce, with lack of information about how propofol could be initiated for palliative sedation, doses and treatment outcomes. Aim To describe the patient population, previous and concomitant medication, and clinical outcome when propofol was used for palliative sedation. Methods A retrospective study with quantitative and qualitative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 20 publications
(22 reference statements)
0
18
0
6
Order By: Relevance
“…Ours is a theoretical exploration of what we anticipate may become a wider phenomenon, observing recent developments in Europe. Early descriptions of this extended use of general anaesthesia using propofol in terminal care by multidisciplinary teams are appearing in the anaesthetic literature [ 49 ]. Mercadante and Giarratano have outlined how the skills of anaesthetists readily map onto many interventions at the end of life [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ours is a theoretical exploration of what we anticipate may become a wider phenomenon, observing recent developments in Europe. Early descriptions of this extended use of general anaesthesia using propofol in terminal care by multidisciplinary teams are appearing in the anaesthetic literature [ 49 ]. Mercadante and Giarratano have outlined how the skills of anaesthetists readily map onto many interventions at the end of life [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Hovedregelen er at alle andre tiltak skal vaere forsøkt før lindrende sedering (9). Imidlertid har palliativ avdeling ved Akershus universitetssykehus utført lindrende sedering parallelt med tilbaketrekking av den livsforlengende behandlingen ved andre diagnoser der rask og sterk økning i plagsomme symptomer var ventet ved avslutning av behandling (10).…”
Section: «Lindrende Sedering Kan Vaere Nødvendig For å Unngå At Pasie...unclassified
“…However, side effects of respiratory depression were found in five cases (31%). Another small retrospective study reported the efficacy of propofol in the use of PS [ 34 ]. All 14 patients achieved sedation and adequate symptom control with respiratory adverse events in two patients.…”
Section: The Practice Of Psmentioning
confidence: 99%